2005
DOI: 10.1177/0898264304268590
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction With Care Among Community Residential Care Residents

Abstract: Measuring satisfaction with community residential care (CRC) is growing in importance but still in its infancy. The authors conducted interviews with 176 CRC residents and their providers. Logistic regression was used to identify resident and physical characteristics, policies and services, and aggregate resident characteristics associated with satisfaction. Residents had high levels of satisfaction, demonstrating most concern with the facility being able to meet their future needs and food quality. Resident d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Furthermore, financial insecurity can be related to an older individual's psychological state. In addition, some studies found that demographic characteristics such as ethnicity, gender, age, and education are significantly associated with the subjective well-being of older adults (Curtis, Sales, Sullivan, Grays, & Hedricks, 2005;Fitzpatrick & Tran, 2002;Winzelberg, Williams, Preisser, Zimmerman, & Sloane, 2005). Particularly, Upchurch and Mueller (2005) reported that educational attainment is a key factor that influences the health of older adults.…”
Section: Socioeconomic Support and Health Of Older Adultsmentioning
confidence: 95%
“…Furthermore, financial insecurity can be related to an older individual's psychological state. In addition, some studies found that demographic characteristics such as ethnicity, gender, age, and education are significantly associated with the subjective well-being of older adults (Curtis, Sales, Sullivan, Grays, & Hedricks, 2005;Fitzpatrick & Tran, 2002;Winzelberg, Williams, Preisser, Zimmerman, & Sloane, 2005). Particularly, Upchurch and Mueller (2005) reported that educational attainment is a key factor that influences the health of older adults.…”
Section: Socioeconomic Support and Health Of Older Adultsmentioning
confidence: 95%
“…, Curtis et al . ). However, high care satisfaction in a special accommodation has been found to be positively associated with perceived health (Chong , Curtis et al .…”
Section: Introductionmentioning
confidence: 97%
“…Cognitive impairment was also associated with higher care satisfaction (Curtis et al . ). Another study showed that better perceived health predicted care satisfaction (Xiao & Barber ), which is in line with findings from Rahmqvist () showing that those who reported poor health were less likely to be satisfied with the public care and service they received (Rahmqvist ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations